HUBUNGAN PEMANFAATAN KLINIK SANITASI DENGAN UPAYA PENCEGAHAN PENYAKIT ISPA DI WILAYAH KERJA PUSKESMAS MAJASEM KOTA CIREBON TAHUN 2019 - Dina Aulya Wahab; Mitha Erlisya Puspandhani; Shella Febiana (Jurnal Kesehatan Mahardika, 2019)
Utilization of clinical sanitation is where people use clinical sanitation room and follow activity in clinical saanitation. Efforts to prevent diseases of the upper respiratory tract, namely to prevent direct or indirect contact with patients with upper respiratory tract infections and using PPE, maintaining environmental cleanliness, maintaining personal hygiene with clean and healthy living behaviors in the household order. Depend on data of Public Health Office Cirebon at 2018, achievement program clinical sanitation just reach clinical sanitation is 30%, number of ISPA cases reach number 26.142 people. This research uses correlation descriptive, approach with cross sectional. Population is all of people in Puskesmas Working Area Cirebon as much 2.506 people. Sample technic which use is purposiv sampling technic as much 97 people. Instrumen which uses this research is questionare. Result of research shows 97 responden total responden which utilize clinical sanitation as much 88 responden or 90,7% more than which not utilize clinical sanitation as much 9,3%. P value which is got as bis as 0,00 and smller of value a = 0,05. This result shows that there is relation utilization of clinical sanitation which prevent ISPA disease in Puskesmas Working Area Majasem Cirebon. Be expected that the agency more improve clinical sanitation program and educate the public related importance to maintain environmental health.